Kontribusi Fasilitas Belajar Dan Persepsi Peluang Kerja Terhadap Minat Memilih Jurusan Akuntansi Di SMK Negeri 1 Punggelan - Arifin, Teni Nur, Dr. Sabar Narimo, MM.M.Pd (2016)
The research is to know the contribution of learningfacilities and the perception of job vacancy toward students interest on accounting in SMK N 1 Punggelan either partiqlly or simultancously. The type of the research is quantitative associative.the population of this research were 178students of tenth grade of accounting at SMK N 1 Punggelan. The sample were 144 students taken by using proportional random sampling. The resear cher used questionaire as technique of collecting data. That has been tested by using validity test and reliability test. The conclution of this is:1) There was significan influence between learning facility to shoose a major interest in accounting by t test was obtained tcount > ttable that is 10,772 >1,982 and significant value < 0,005 is 0,025. 2 ) There was significan influence between perception of job opportunities to choose a major interest in accounting by t test was obtained tcount > ttable that is 5,956 >1,982 and significant value < 0,005 is 0,025.3) There is a significant relationsip between learning facilities, job opportunities to shoose what interest accounting majors based test known f, fcount > ftable is 135,141 > 3,078 with significant value 5%. The result of the conclution of the value (R2)acquired 70,9% interest in selecting thr accounting dapertment ininfluened by the perception of learning facilities and employment opportunities remaining 29,1% is influenced by other variables not examined in this research.